2016
DOI: 10.1016/j.watres.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of current generation and electrolyte pH on reverse salt flux across thin film composite membrane in osmotic microbial fuel cells

Abstract: a b s t r a c tOsmotic microbial fuel cells (OsMFCs) take advantages of synergy between forward osmosis (FO) and microbial fuel cells (MFCs) to accomplish wastewater treatment, current generation, and high-quality water extraction. As an FO based technology, OsMFCs also encounter reverse salt flux (RSF) that is the backward transport of salt ions across the FO membrane into the treated wastewater. This RSF can reduce water flux, contaminate the treated wastewater, and increase the operational expense, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…To improve our understanding of enhanced electricity generation in OsMFCs, a mathematical model has been developed and used to predict a reduction of internal resistance with increasing osmotic pressure gradient and water flux, thereby confirming the enhanced current generation (Qin et al, 2015). It was also reported that in an OsMFC, reverse salt flux 5 (RSF), which is backward transport of salt ions across the FO membrane into the treated wastewater, was significantly inhibited by the current generation (Qin et al, 2016a).…”
Section: Introductionmentioning
confidence: 96%
“…To improve our understanding of enhanced electricity generation in OsMFCs, a mathematical model has been developed and used to predict a reduction of internal resistance with increasing osmotic pressure gradient and water flux, thereby confirming the enhanced current generation (Qin et al, 2015). It was also reported that in an OsMFC, reverse salt flux 5 (RSF), which is backward transport of salt ions across the FO membrane into the treated wastewater, was significantly inhibited by the current generation (Qin et al, 2016a).…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that bioelectricity generation in an OsMFC could significantly reduce RSF. When the total Coulomb production increased from zero (open circuit) to 311 C, RSF was reduced from 16.3 ± 2.8 to 3.9 ± 0.7 gMH (Qin et al 2016a). …”
Section: Figure 24 Mutual Benefits Between Bes and Fo In Osbesmentioning
confidence: 99%
“…A previous study has reported that the cation flux could be increased when sodium was in the feed solution and ammonium was in the draw solution in FO process, resulting from the ion exchange of cation ions (Lu et al 2014a). But bioelectricity generation in an OsMFC could greatly inhibit back flux of cations (e.g., sodium ions) from the draw into the feed (Qin et al 2016a) and facilitate forward movement of ammonium from the feed into the draw. Our analysis showed that ion exchange was not a major contributor to ammonium movement in the present OsMFC (more details in next section).…”
Section: Effects Of Water Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the movement of electrons (electrically driven) could affect ion transport across FO membrane. Compared to the open circuit (no electricity generation), a closed circuit mode can facilitate the forward transport of cations (from the anode to the cathode) in the OsMFC due to the electrons moving from the anode electrode to the cathode electrode, resulting in decreased reverse cation diffusion; this decreased cation transport would repel the reversed anions transport for charge balance, leading to the reduction of RSF . Prior studies have screened for appropriate DS for FO applications and studied 14 DS selected from more than 500 inorganic compounds .…”
Section: Introductionmentioning
confidence: 99%